THE IMPLEMENTATION OF GBA IN WRITTEN CYCLE TEACHING TO IMPROVE STUDENTS' RECOUNT TEXT WRITING ABILITY: A Quasi-Experimental Study Conducted in a Senior High School in Subang - Sinan, Zahra Faula (2014)
This study aims to investigate whether the implementation of genre based approach especially in the written cycle can improve students' writing ability particularly in writing a recount text and to find out students' responses towards this implementation. The study employs a quasi-experimental design by using non-equivalent control group pre-test and post-test design. This study was conducted in a private senior high school in Subang and involved two classes of tenth grade students. One class was treated as a control group and the other was treated as an experimental group that received a treatment, a written cycle of genre based approach. The data of the study were gathered from a pretest, a posttest, and a questionnaire as the main data and an interview which was used to convince the questionnaire's data. The pretest and the posttest scores were computed by using SPSS 17 for Windows. The results show that the genre based approach can improve students' recount text writing ability as indicated by the experimental group's mean which is highly improved (pretest = 61.36, posttest = 84.8). Those data are supported by the students' responses towards GBA through the questionnaire which received positive responses. Based on the findings, it is recommended that the genre based approach be applied to improve students' writing ability. Penelitian ini bertujuan untuk mengetahui penerapan genre based approach dengan menggunakan model pengajaran written cycle untuk melihat peningkatan kemampuan menulis siswa khususnya dalam menulis teks recount dan juga untuk mengetahui pendapat siswa tentang penerapannya. Penelitian ini menerapkan metode quasi eksperimen dengan menggunakan pretest dan posttest. Penelitian ini dilaksanakan di salah satu sekolah menengah atas di Subang dan melibatkan dua kelas dari kelas sepuluh. Satu kelas dijadikan sebagai grup kontrol dan kelas lainnya dipilih sebagai grup eksperimen yang mendapatkan percobaan, penerapan model pengajaran written cycle. Data penelitian diperoleh dari pretest, posttest dan data kuesioner sebagai data utama dan data interview sebagai penguat dari data kuesioner. Perhitungan pada data pretest dan posttest menggunakan SPSS 17 for Windows. Data yang diperoleh dari perhitungan tersebut secara statistik membuktikan bahwa genre based approach dapat meningkatkan kemampuan siswa dalam menulis teks recount yang ditunjukkan dengan nilai mean dari grup eksperimental yang mengalami peningkatan nilai yang cukup tinggi (pretest = 61.36, posttest = 84.8). Data tersebut juga diperkuat oleh pendapat siswa melalui kuesioner mengenai penerapan genre based approach yang mendapatkan respon positif. Dari data-data yang diperoleh dalam penelitian ini, disimpulkan bahwa penerapan genre based approach untuk meningkatkan kemampuan menulis siswa sangat dianjurkan.